PP.LB02.14: THE POSITIVE INFLUENCE OF EARLY MANAGEMENT OF BLOOD PRESSURE IN PATIENTS WITH DIABETES MELLITUS IN THE APPEARANCE OF MAJOR CARDIOVASCULAR EVENTS. (June 2015) - Krezias, P.; Sianni, A.; Ganotopoulou, A.; Martsoukis, K.; Paraskevas, P.; Gova, E.; Kostaki, C.; Masgala, A.; Milonas, P.; Asimis, A.; Karapati, I.; Tsivilis, N.; et al.
Abstract : Objective: To study the effect of early blood pressure(BP)control in patients with diabetes mellitus(DM) with recent onset of hypertension in relation to cardiovascular risk. Design and method: Krezias P, Sianni Alexandra1, Ganotopoulou Asimina2, Matsoukis, KostantiCh.1, Paraskevas Polichronis1, Gova Eleni1, Kostaki Constantina1, , Masgala Aik, Liouris Ioannis1 Internal Medicine Department, 1.Konstantopoulio General Hospital of Nea Ionia, Athens 2.Tzanio General Hospital of Piraeus, GREECE. The study included 252patients, age 67 ± 5years, out of which 148(59%) were men and 104 (41%)were women. All participants suffered from DMtype2 and met the criteria of recent onset hypertension(not receiving antihypertensive treatment and had episodes of elevated BP during the last six months before the initiation of the study).None of them had coronary or cerebrovascular disease in their medical history at the beginning of the study. Patients were divided into three groups according to the levels of BP at the first year of the study:Group A included 84patients with BP > 165/95mmHg, Group B included 96 patients with 140/85 < BP < 160/90mmHg and group C included 72participants with BP < 140/85mmHg. The study duration was 3 years and BP, HbA1c and the incidence of major cardiovascular events were examined at 6, 12, 18, 24and 36months. Results: In Group A, cardiovascular events were observed in 16patients(19%):12 of them were men(75%) and 4 were women(25%). Among the male group, 8 participants had a myocardial infraction and 4 had a stroke.All 4 female participants had a stroke as major cardiovascular event. In Group B, out of a total of 8 cardiovascular events(8.3%), 6 female participants had a myocardial infraction and 2 female patients had a stroke.In Group C only 2 major events, namely myocardial infraction, occurred in 2 male participants with diabetes(2.7%). Conclusions: Early and adequate blood pressure control, especially in the first year after the diagnosis of hypertension, reduces the risk of major cardiovascular events in diabetic patients.